The Mechanism of High-Strength Quenching-Partitioning-Tempering Martensitic Steel at Elevated Temperatures - Ke Zhang (Crystals, 2019)
High-strength medium-carbon martensitic steel was heat treated through a quenching-partitioning-tempering (Q-P-T) treatment. Both the mechanism for improved ductility and the high temperature stability of austenite were investigated. The Q-P-T martensitic steel showed good products of strength and elongation (PSE) at various deformation temperatures ranging within 25⁻350 °C. The optimum PSE value (>57,738 MPa%) was achieved at 200 °C. The microstructure of the Q-P-T steel is constituted of laths martensite with dislocations, retained austenite located within lath martensite and small niobium carbides (NbC), and/or transitional ε-carbides that precipitated in the lath martensite. The good ductility can be mainly attributed to the laminar-like austenite that remained within the lath-martensite. The austenite can effectively enhance ductility through the effect of dislocation absorption by the retained austenite and through transformation-induced plasticity. The relationship between the microstructures and mechanical properties was investigated at high deformation temperatures.